2007
DOI: 10.1007/s00125-006-0578-8
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the associations between functional β2-adrenergic receptor variants and obesity, hypertension and type 2 diabetes in 7,808 white subjects

Abstract: Aims/hypothesis Functional and common Arg16Gly and Gln27Glu polymorphisms have been identified in ADRB2, the gene encoding the β 2 -adrenergic receptor. These variants have previously been examined for association with obesity, hypertension and diabetes with inconclusive results. Materials and methods We investigated both of these variants in 7,808 unrelated, middle-aged white people for their association with obesity in a case-control study, quantitative trait analysis and meta-analysis. Moreover, both varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 30 publications
(51 reference statements)
3
59
2
Order By: Relevance
“…Noteworthy, Arg16/Gln27 patients were on average 10 y younger, more often had an ischemic cause of their cardiomyopathy, and more often had hypertension and diabetes mellitus. Apart from the difference in age, these observations are in line with previous studies (12,32,33). The reason for the difference in age is unclear, since the Arg16/Gln27 haplotype does not influence survival in patients with HF (34) and seems not to be a risk factor for HF (35).…”
Section: Discussionsupporting
confidence: 88%
“…Noteworthy, Arg16/Gln27 patients were on average 10 y younger, more often had an ischemic cause of their cardiomyopathy, and more often had hypertension and diabetes mellitus. Apart from the difference in age, these observations are in line with previous studies (12,32,33). The reason for the difference in age is unclear, since the Arg16/Gln27 haplotype does not influence survival in patients with HF (34) and seems not to be a risk factor for HF (35).…”
Section: Discussionsupporting
confidence: 88%
“…To avoid reporting bias, we contacted the authors for raw data. We acquired the data, including 6495 Caucasian subjects from Gjesing et al, 20 but failed to gain information from two original studies 31,32 of Asians, which included 1700 subjects altogether. These two papers both indicated 'negative' results of A46G and C79G polymorphisms, which were consistent with our results of meta-analysis in Asians and overall.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]27,28 Of the 19 eligible articles, the study of Gu et al 28 was replaced by their earlier report, 10 as these two articles reported the same data. Wu et al 5 provided data on two Chinese minorities, the Hani and Yi, residents of the remote rural area of Yunnan, China.…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Discordance between 938 random duplicate samples was Ͻ0.85%, and the genotyping success rate was Ͼ96%. For gene-gene interaction studies, the IRS1 Gly971Arg (rs1801278) and ADRB2 Arg16Gly and Gln27Glu (rs1042713 and rs1042714) (22) polymorphisms were also analyzed. Genotyping of the variants was performed using Taqman allelic discrimination or chip-based matrix-assisted laser desorption/ionization time-of-flight mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%